1312. Clinical and Economic Burden of Otitis Media in Children under 5 in the United States. (15th December 2022) - Debba, Lilia Ben; Derreumaux, Dominique; Pickett, Jessica; Taddei, Laura; Beck, Ekkehard; Scherbakov, Michael
Abstract: Background: Otitis media (OM) is one of the most common childhood illnesses and frequent cause of antibiotic use among patients under 5 years old. Pneumococcal conjugate vaccines (PCVs) led to a reduction in the burden of OM caused by Streptococcus pneumoniae (Spn) strains in the United State (US). Overall, OM incidence was reduced after introduction of PCV7 and plateaued in the late PCV13 era, though there was an increase in OM episodes caused by non-typeable Haemophilus influenzae and non-vaccine-type Spn . The objectives of this study were to assess the incidence and treatment costs of OM episodes and their complications in the US. Methods: This retrospective observational study used data from IBM MarketScan to study pediatric OM incidence and complications (tympanostomy tube placement [TTP], hearing loss [HL] and hospitalizations) by age groups and their associated costs. OM episodes occurring between January 1, 2016, and December 31, 2017, were considered in this analysis. Results of the total cost are weighted by the proportion of children covered under commercial insurance and Medicaid, respectively. Results: The incidence of OM among children < 5 increased gradually with age, reaching a peak of incidence between 1 and 2 years (figure 1) and more precisely between 6 and 15 months. Overall, most OM episodes were without HL and treated in an outpatient setting without TTP (∼ 94% of cases); OM episodes without HL requiring TTP represented only 4% and the vast majority were performed in an outpatient setting ( > 99%). OM without HL leading to hospitalization was very rare (< 0.025%) for both plans. OM leading to HL corresponds to 2% of all OM episodes. The incidence rate and the mean cost per episode were used to extrapolate an overall economic burden of ∼5 billion USD in 2020, driven by outpatient episodes (50%) followed by OM episodes plus TTP (37%), and OM episodes plus HL (13%). Figure 1: Incidence rates by age groups for (A) Commercial/Medicare; (B) Medicaid Conclusion: The burden associated with OM in children < 5 reflects a significant and ongoing unmet need. Thus, prevention of OM not currently covered by existing vaccines is warranted to address the significant burden including the potential emergence of antimicrobial resistance. Funding: GlaxoSmithKline Biologicals SA (GSK study identifier: VEO-000264]) Disclosures: Lilia Ben Debba, PharmaD, GlaxoSmithKline SA: Advisor/Consultant Dominique Derreumaux, M.Sc, GlaxoSmithKline SA: is employed by the GSK group of companies Jessica Pickett, PhD, GlaxoSmithKline SA: is employed by and hold shares in the GSK group of companies Laura Taddei, M.Sc, GlaxoSmithKline SA: is employed by and hold shares in the GSK group of companies Ekkehard Beck, PhD, GlaxoSmithKline SA: is employed by and hold shares in the GSK group of companies Michael Scherbakov, PhD, GlaxoSmithKline SA: is employed by and hold shares in the GSK group of companies.